Technology in its place : (Jossey-Bass, 2001)
Technology in Its Place is a practical resource that features diverse approaches for improving teaching and learning through the use of technology. The contributors are a blue-ribbon panel of experts in the field who cover a broad range of topics including information on administration, strategic planning, leadership, curricular integration, and professional development.